Preservação de acervos especiais nas bibliotecas de universidades federais do Brasil: a digitalização como processo para viabilização do acesso à informação - Nóbrega, Hugo Araújo da (2021)
This paper aims to identify how the federal universities in Brazil, through their libraries, digitize their special collections and make them available, preserving them and make them more accessible to society. To achieve this purpose, the following specific objectives are defined: highlight the importance of the special collection for university libraries as social memory; reinforce the importance of digitizing special collections to enable access to information; map which universities, among the different regions of Brazil, have special digitalized collections; and find out which special materials are commonly digitized by these institutions. This study aims to understand the level of preservation of special collections in Brazilian federal universities, considering the fragility of these materials and their access limitations within libraries. Methodologically, this research is characterized as an applied study, with exploratory and descriptive methods, having a quantitative and qualitative approach, besides contemplating the procedures of bibliographical research and case study. The results show that some Brazilian federal universities invest in digital preservation, using digital repositories. Finally, this investigation concludes that digitization is a valid method for the preservation of special collections and also for the maintenance of institutional memory in Brazilian universities.